The sound design of Launderama - Lee, Celine Qian Hui (Nanyang Technological University, 2020)
As the Director of Sound for the Final Year Project film titled Launderama, my role was to ensure that the sound design of the film was believable and that it would push the story forward. This encompassed making creative decisions throughout pre-production, production and post-production. This report serves as a documentation of how I fulfilled my responsibilities at each stage of the project and a record of my thought process.